THE ELEMENTS OF A MYTH IN OLD GREEK NOVEL “DAPHNIS AND CHLOE” BY LONGUS - Chakal (Makar), Inesa (My University, 2014)
Longus, the ancient greek writer of the end of the second century, which wrote the pastoral novel „Daphnis and Chloe”, lived in the epoch of the „second sophistry”, when artistic and moral values were actively overvalued, in the epoch, when vision and treatment of religion was changed and rural gods, Pan and Nymphs, were honoured only as a tradition and mainly among villagers. Longus’ attitude toward religion and beliefs was serious enough: faith in gods’ existence and worship to the cult of deity are real for him, and images of gods and narrations about wonders, which they create, are not just an addition to artistic narrative, but an important part of it. Also appears a necessity to examine the dedication of the novel as a gift to Eros, Nymphs and Pan. We consider the elements of myth not an artistic reception, but an important component of the writer’s idiostyle, his world outlook. A question about using of mythical elements in the Longus’ novel, that was the subject of our scientific research, we consider to be actual.
Keywords: myth; pastoral novel; religious tradition; Nymphs; Pan; Eros; idiostyle